Plasma-electrolyte discharges in a gas-liquid medium for the production of hydrogen - A. F. Gaysin; F. M. Gaysin; L. N. Bagautdinova; A. A. Khafizov; R. I. Valiev; E. V. Gazeeva (Известия высших учебных заведений: Проблемы энергетики)
THE PURPOSE. Comprehensive study of the effect of direct current electric discharge plasma in a gas-liquid medium of inorganic mixtures in order to obtain gaseous hydrogen. Obtain volt-ampere, volt-second and ampere-second characteristics of the discharge at various concentrations of electrolyte. Study the process of electrolysis, breakdown, discharge ignition and discharge flow in a dielectric tube at a constant current. METHODS. To solve this problem, experimental studies were carried out on a model installation, which consists of a power supply system, a discharge chamber, equipment for monitoring and controlling the operation of the installation and measuring the characteristics of an electric discharge. To analyze the stability of the discharge, the time dependences of the voltage ripple and the discharge current were obtained. RESULTS. Experimental studies were carried out between the electrolytic cathode and the electrolytic anode at constant current and at atmospheric pressure with the following parameters: discharge voltage U = 0.1-1.5 kV, discharge current I = 0.02-2.3 A, interelectrode distance l = 100 mm , 1%, 3% and 5% solutions of sodium chloride in tap water were used as electrolytes. CONCLUSION. It is shown that electrical breakdown and ignition of a discharge that is stable in time depends on the conductivity of the gas-liquid medium of the electrolyte. The nature of the current-voltage characteristics depends on the random processes occurring in the gas-liquid medium, which is associated with numerous breakdowns occurring in the gas-liquid medium of the electrolyte, combustion and attenuation of microdischarges, the appearance of bubbles, and the movement of the electrolyte inside the dielectric tube. It is shown that the generation of hydrogen and hydrogen-containing components can occur both at the stage of electrolysis and during discharge combustion. A feature of this method is that electrical discharges in the tube increase the release of hydrogen. In this installation, inorganic and organic liquids of a certain composition and concentration can be used. The results of experimental studies made it possible to develop and create a small-sized installation for producing gaseous hydrogen. Tests have shown that a small-sized plant can be taken as the basis for a industrial plant for the production of hydrogen gas.